Analisis Pengaruh Perubahan Penggunaan Lahan Terhadap Perubahan Tingkat Potensi Gerakan Tanah Menggunakan Sistem Informasi Geografis Di Kecamatan Mojosongo Kabupaten Boyolali - Wasisso, Tomi Yogo; , Dr. Kuswaji Dwi Priyono, M. Si (2017)
Changes in land use that occurred in the district Mojosongo, Boyolali regency has the potential to affect the potential for ground movement. The purpose of this study is (1) to identify changes in land use, (2) identifying changes in the level of potential ground movement, and (3) an analysis of the effect of land use change on changes in the level of potential ground motion. The method used in the study was a survey, with analysis to achieve the objectives are: (1) conduct a qualitative descriptive analysis of the land use map in 2006 and land use maps in 2016, (2) conduct quantitative descriptive analysis tiered weighted to map the level of potential ground movement in 2006 and map the level of potential ground movement in 2016, and (3) conduct descriptive analysis of qualitative effect of land use change on changes in the level of potential ground motion. Results of the study are: (1) a map of land use change, with the greatest changes in land use are: the gardens to the settlement of 541,43ha or 12.34%, (2) map changes in the level of potential ground movement, with changes in the level of potential ground motion greatest are: from low to high for 512,91ha or 11.69%, and (3) Changes in land use change potential ground motion are: changes in land use to settlement and moor to the settlement.